2022
DOI: 10.1177/13623613221138643
|View full text |Cite
|
Sign up to set email alerts
|

Cost-benefit analysis of a non-government organization and Australian government collaborative supported employment program for autistic people

Abstract: We present a cost-benefit analysis of an Australian Government sponsored 3-year supported employment program for autistic adults—the DXC Dandelion Program—in the information and communications technology sector. We explored the range of direct costs associated with running the program, benefits to participants, and avoided costs to the government. Estimates were based on data from 56 (86% men; Mage = 25.28, standard deviation [SD]  = 8.36 years) autistic participants in the program. The program generated a hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…While unemployment as a proportion of the labor force did fluctuate significantly across waves, it did not always differ from the general population. In previous research autistic people report higher rates of underemployment as well as unemployment in relation to the match between their level of vocational training and employment (Baldwin et al, 2014; Hedley et al, 2023) or hours worked (Roux et al, 2013). Consistent with others (Baldwin et al, 2014; Frank et al, 2018), roughly one third of participants reported that their employment was completely on parity with their level of education.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…While unemployment as a proportion of the labor force did fluctuate significantly across waves, it did not always differ from the general population. In previous research autistic people report higher rates of underemployment as well as unemployment in relation to the match between their level of vocational training and employment (Baldwin et al, 2014; Hedley et al, 2023) or hours worked (Roux et al, 2013). Consistent with others (Baldwin et al, 2014; Frank et al, 2018), roughly one third of participants reported that their employment was completely on parity with their level of education.…”
Section: Discussionmentioning
confidence: 87%
“…The autistic population is characterized by low employment rates (e.g., 28% Australia; Australian Bureau of Statistics, 2019; 14% US; Roux et al, 2017; 32% UK; The National Autistic Society, 2016; 14% Canada; Zwicker et al, 2017), reduced working hours, or positions poorly matched to skills or qualifications (Hedley et al, 2023; Zwicker et al, 2017). Little is known about vocational activities by gender, age, or compared to the general population (Shattuck et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In Western countries where data are available, this is reflected in low rates of employment (e.g. 27.3% in Australia, Australian Bureau of Statistics, 2019; 14% in the United States & Canada, Roux et al, 2017;Zwicker et al, 2017) compared to nonautistic populations and high rates of underemployment or working in roles that do not match skills or training (Hedley et al, 2023).…”
mentioning
confidence: 99%
“…This latter point may be justified, as disclosure of an autistic identity has been found to impact employer perceptions of a simulated autistic employee ( Flower et al, 2021 ). However, autistic people who are provided with a supportive work environment, including physical or sensory accommodations, supportive colleagues and job roles that are well-matched to their interests and skills, are often reliable and high-performing ( Hedley et al, 2023 ). Indeed, Hedley et al (2023) found that, when provided with appropriate supports (as part of an industry-led supported employment programme), a majority of unemployed autistic people were able to transition to stable, open employment that was matched to their skills and qualifications.…”
mentioning
confidence: 99%
See 1 more Smart Citation